Between Hemse and Mästermyr: Craft interpretations of two findings from Gotland - Almevik, Gunnar; Pärmsten, Bertil; Sjöholm, Magnus (FormAkademisk, 2021)
The distance between Hemse church and the fields of Mästermyr on the Swedish Island of Gotland is about eight kilometers. The distance or rather the proximity between these two places is given importance in this filmed research article. In the 1930s, a farmer found a wooden chest in Mästermyr containing hundreds of forged tools and other artefacts. During a restoration of the Romanesque Hemse church in the 1890s, reused parts of a stave church were discovered in the wooden floor. The hypothetical question that is investigated in this study is whether the tools from Mästermyr were used in the construction of Hemse stave church in the early 1100’s? This filmed article analyzes and compares the traces of toolmarks in Hemse stave church and the woodworking tools from the Märstermyr finding. Through a forensic examination involving 3D scanning with structured light, 3D printing and reconstruction of tools and woodworking procedures, it is revealed that several toolmarks in the stave church correspond to the characteristics of woodworking tools in the Mästermyr find. The tool's shape, dimensions and mode of operation are traced in its negative imprint in the stave church’s oak wood.